Determinants Of Financial Shenanigans Indications During The Covid-19 Pandemic - Majidah Majidah; Novy Aryanty (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2022)
This research aims to determine determinants of financial shenanigans and the differences in indications of the occurrence of financial shenanigans before and during the Covid-19 pandemic. Data of manufacturing industry listed on the Indonesia Stock Exchange (IDX) during 2019-2020 analyzed using descriptive statistical and logistic regression. The results show that financial targets, characteristics of the chief financial officer, and financial stability were simultaneously determinants of financial shenanigans. Partially, financial targets were the only determinants of financial shenanigans and no significant differences in indications of financial shenanigans before and during the Covid-19. Results of this study can be utilized by external auditors in detecting indications of financial fraud through changes in financial targets and can be an inform for investment decisions. Future study should consider continuing testing variables that do not have an effect by bringing up other calculation indicators and extend the time span either sample to predict financial shenanigans.